The Role Of Relationship Learning As The Mediator Of The Market Orientation Impact Toward Competitive Advantage And Marketing Performance Of The Furniture Companies In Java Island - Wijaya, Oscarius Y.A (Program Doktor Ilmu Ekonomi, 2013)
Relationship learnings is the main essential requirement to create company’s innovation power to enhance its competitive advantage. The relationship learning of furniture compa-nies in Indonesia has been considered in low level compared to China and other Asian countries. This also has a significant effect toward marketing performance in term of bilateral trade relationship between Indonesia and China. The link phenomenon of market orientation with the awareness about relationship behavior of furnitures companies in China has much more dominant role to win the competition. The connection or network (Guan Xi - 关系) has been used to maintain business relation amongst furniture companies in China for information sharing from academicians, suppliers and even competitors. Apparently, furnitures companies Indonesia haven’t got used to it. Companies here are less paying atten-tion on this remarkable source to generate a new innovation or design, even making market surveys to support innovation capability. The purpose of this research is to analize the followings, (1). The effect of market orientation toward relationship learnings, (2). The effect of market orientation toward competitive advantage, (3). The effect of relationship learning toward competitive advantage, (4). The effect of market orientation toward marke-ting performance, (5). The effect of relationship learning toward marketing performance, (6). The effect of competitive advantage toward marketing performance of furnitures com-panies in Java island region.The research objects are all furniture companies in Java island region which consists of Surabaya, Semarang, Bandung and Jabodetabek with total number about 830 companies, with furniture company as analysis unit. 90 companies were being taken for the samples. This research has using SEM (Structural Equation Model) as the analysis tool to estimate the reciprocal effect by involving interverning variable. The analysis’ results showing that the market orientation has a possitive effect to marke-ting performance of furnitures companies in Java island region thru relationship learning.Keyword: market orientation, relationship learnings, competitive advantage, marketing performance